ANALISIS KEPATUHAN PENERAPAN AKUNTANSI PERSEDIAAN PADA PT. MAKASSAR MANDIRI PUTRA UTAMA (BETA BERLIAN) MANADO - Windah, Nadia Marcella; Karamoy, Herman; Suwetja, I Gede (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Merchadise Inventory is assets available for sale in normal activity of company. Inventory is the biggest current assets compare to the other asset. The main problem in the inventory accounting is inventory recording and valuation of inventory. These are matters that encourage the author to do research about, are the implementation of inventory accounting of Makassar Mandiri Putra Utama (Beta Berlian) Company in Manado has done according to Statement of Financial Accounting Standards (SFAS) 14 about inventories. In this research the writer uses the descriptive qualitative method. Methods of collecting data by interview, observation and documentation. The types of data collected by the author are secondary and primary data. Makassar Mandiri Putra Utama (Beta Berlian) Company in Manado is a company that engaged in the sale of various types of Mitsubishi cars. The result found by the author shows that PSAK number 14 has been implemented thoroughly comprised recording and inventories analyzing according to the Â Financial Accounting Standards Keyword: Accounting Inventories, Recording and Valuation Method, PSAK 14